The Effect of the Proportion of Tapioca Flour with Chicken Leg Skin and Bones on the Quality of Chicken Leg Crackers - Dendy Kurnia Putra; Basori Basori (Universitas Muhammadiyah Sidoarjo, 2014)
Barefoot processing is widely used as food products in Indonesia and one of the products is cracker. Therefore, production of high quality cracker is required to study the proportion of ingredients. The aim of this study was to determine the best proportion of tapioca, chicken skin and chicken leg bone towards cracker quality. The cracker was treated based on proportion (g) of tapioca, chicken skin and chicken leg bone as follows: T1 (100:50:0), T2 (100:0:50), T3 (100:25:25), T4 (100:33:17), T5(100:17:13), T6 (80:70:0), T7 (80:0:70), T8 (80:35:35), T9 (80:47:3), T10 (80:23:47). The experiment was arranged by randomized block design (RBD), which were run triplicate, thus all samples were obtained 30 experiment units. The observed variables were classified by chemical analysis (protein, water, Ca), physical analysis (degree of expansion and mass expansion), and sensory evaluations (color, aroma, flavor and crispiness). The data was analyzed using ANOVA followed by HSD 5 % and the organoleptic were analyzed by Friedman test. The results were significantly different based on protein and color. However, the datas were not significantly different based on taste, aroma, crispiness, degree of expansion and mass expansion. T5 was identified as best characteristic, notably the proportion of tapioca:chicken skin:chicken leg bone was 100:17:33. Its characteristic based on protein, moisture, calcium, mass expansion, degree of expansion were 3.96 %, 10.24 %, 176.8 mg/100g, 0.20 %, and 5.97%, respectively. In the other hand, sensory value based on color, aroma, flavor and crispiness were 5.07 (like), 4.7 (rather like), 5.03 (like), and 5.33 (like), respectively.